Hubungan Determinan dengan Kualitas Hidup dan Outcome Terapi pada Pasien Gagal Ginjal Kronis Dengan Hemodialisis di RS Pku Muhammadiyah Surakarta: Penelitian - Pradina Arifah Nurcahyani; Kharisma Jayak P; Anna Fitriawati (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
The purpose of this study was to determine the quality of life and outcome of therapy for Chronic Kidney Failure patients undergoing hemodialysis at PKU Muhammadiyah Surakarta Hospital, the frequency distribution of each factor, and to analyze the relationship between each factor and the patient's quality of life. This research method is a correlation with a cross-sectional approach involving 71 respondents of CKD patients undergoing hemodialysis. This study used primary data using the WHOQOL questionnaire and laboratory data. The results of the study were that most respondents had a good quality of life 52%, 70% of respondents were male, 59% were elderly, 51% had completed their last education at high school/vocational high school, and 63% were working. The results of the Spearman Rank test showed no significant relationship between the determinants, namely between age and gender factors with patient quality of life, and between therapy outcomes with patient quality of life, but there was a relationship between education and employment factors with the quality of life of Chronic Kidney Failure patients.